Feasibility of calculating rocuronium dosage by skeletal muscle weight in patients with obesity - Hu, Zhenhua; Li, Benmu; Li, Zhanwen; Liu, Zhe; Liu, Shengqun (Frontiers in Medicine, 2024)
This study aimed to investigate the dose–response relationship of rocuronium administered based on skeletal muscle weight and to assess the feasibility of calculating rocuronium dosage by skeletal muscle weight in short surgeries for patients with obesity. This single-center, randomized controlled clinical trial included 71 patients with obesity aged 28–70 years, with body fat percentages (PBF) >20% in men and > 28% in women, ASA status I-III, scheduled for tracheoscopy. Patients were randomly allocated into two groups: skeletal muscle group (SM group) received rocuronium based on the skeletal muscle content (1.0 mg/kg, n = 31), and the conventional administration group (conventional group) received rocuronium based on total body weight (0.45 mg/kg, n = 30). General anesthesia was administered using the same protocol. Parameters recorded included patients’ general condition, muscle relaxant usage, onset time of muscle relaxants, non-response time, clinical effect time, 75% recovery time, and recovery index. Additionally, occurrences of body movement, choking, and incomplete muscle relaxation during surgery were recorded. Compared to the conventional group, the SM group required significantly less rocuronium dosage, resulting in significantly lower non-response time, clinical effect time, 75% recovery time, and recovery index (p < 0.05), and the onset time is slightly longer. Neither group experienced body movement, choking, or incomplete muscle relaxation (p > 0.05). Utilizing skeletal muscle weight to calculate rocuronium dosage in short surgeries for patients with obesity can reduce dosage, shorten recovery time, and prevent residual muscle relaxation while achieving satisfactory muscle relaxation to meet surgical requirements.